Ethology and production of freshwater crayfish in aquatic polysystems in Western Australia - Storer, Timothy (Curtin University, 2005)
Aquatic polyculture has been recognised as a potential way of increasing the costeffectiveness of farming marron (Cherax tenuimanus), as it can lower average costs of production, increase system yields, and reduce economic risks associated with monoculture operations. Polyculture also increases ecological stability and assists recycling processes, which can result in synergistic benefits to participating species. In aquaculture, this synergism can result in increased profitability through advanced growth rates and/or reduced feed input. However, many of the inherent advantages of aquatic polyculture rely on cohabitants occupying distinct ecological niches within the system. In Western Australia, opportunities to multi-crop aquatic species are limited by species choice due to low natural diversity and strict translocation policies. This creates a situation where available aquaculture species exhibit overlaps in occupied niches. Effects of this overlap can include direct predation, increased intraspecific conflict, and competition for resources such as shelter and food. Prior to this study, silver perch (Bidyanus bidyanus) were identified as a prime candidate for duoculture with marron, based on favourable schooling and feeding characteristics, and preliminary trials demonstrated commercial benefits, including synergistic growth advantages to marron. However, investigations also showed that silver perch will predate on both small and moulting crayfish under certain conditions, and that growth of silver perch was inhibited when held in cages to prevent predation. The work reported in this thesis was undertaken to address the niche overlap existing between marron and silver perch, and therefore assist the marron industry in Western Australia in implementing appropriate management strategies for diversification.Research focussed on investigating the ecological issues underlying interspecific interactions in marron polysystems, with the eventual aim of presenting information that could assist system managers in determining optimal conditions required to reduce antagonistic relationships and maximise synergism, ultimately leading to higher yields. Seven trials were conducted in three culture systems (54L aquaria, 250L aquaria and 720m2 experimental ponds) examining the ability of marron to detect, recognise and respond to a range of information cues (chemical, visual, tactile) from two potential predators (silver perch and Murray cod), with and without competition from conspecific and heterospecific crayfish (Cherax albidus). The ability of marron to interpret and respond appropriately to these variables was tested under a range of system-specific conditions, including stocking density, stocking size, shelter/habitat complexity, food availability, light intensity and life stage. Cage culture conditions were also examined to determine if the addition of shelter would mediate growth inhibition previously recorded, and to determine the desired stocking regime to return market sized fish in one growth season (8 months). Results from laboratory research and field-based trials did not support the free-range culture of marron and silver perch, even where turbidity and habitat complexity is high. Although both male and female marron (various sizes) demonstrated an ability to detect and differentiate between chemical and visual cues from potential predators, avoidance responses were only displayed upon attack from predators, or following predation of conspecifics; and avoidance strategies employed by marron were relatively ineffective.Although marron showed some capacity to recognise an impending predatory threat, high initial mortalities and growth inhibition due to reduced foraging, would greatly reduce system yields. In addition, intraspecific competition between marron is likely to increase as avoidance responses would lead to high relative densities within shelters. The lack of avoidance behaviour displayed by marron when only visual and chemical cues from predators are present strongly supports cage culture of silver perch in marron ponds. As marron did not appear to alter their general behaviour (e.g. foraging) based on cues associated with silver perch held in cages they stand to benefit from cohabitation. Field-trials examining the pond culture of marron and caged silver perch demonstrated synergistic growth advantages to marron, compared to monoculture, and also identified several system variables that appear to improve polyculture production. The addition of bank shelters (within 1m of waters edge) was suggested to give marron a competitive advantage when moulting, expressed through growth and survival. Survival of marron was also increased in caged polyculture ponds, compared to monoculture, most likely due to increased health status (due to improved recycling) and/ or increased habitat complexity owing to the presence of fish cages. Growth inhibition previously reported when silver perch are held in cages was mediated to some degree by cage shelters, which appeared to increase feeding behaviour, reduce general anxiety and resulted in increased growth. The introduction of advanced silver perch fingerlings in order to produce market-sized fish in one growth season was also supported. However, it is recommended that cage culture dynamics require further elucidation if silver perch are to be commercially successful as a stand-alone crop using this growout strategy.Significantly, the synergistic growth advantages experienced by marron when grown with fish demonstrate value from polyculture even if fish are not depended on as a secondary income. In this case, other species may also provide similar advantages, and a native candidate such as freshwater cobbler (Tandanus bostocki) would also redress problems associated with translocation laws restricting the use of silver perch in some areas of Western Australia. As no density effects were recorded in any of the trials conducted for either species, further investigation into increased system loads is required. In addition, as nutrient loads, and thus phytoplankton density, usually increases proportionately with pond biomass it is recommended that an additional herbivorous species, for example white eye mullet (Mugil cephalus), be examined in conjunction with increased density trials. Field research reported in this thesis was carried out in earthen ponds utilising remediated water from a acidified mine lake. Over a three-year period water quality parameters were maintained within optimal ranges for marron and silver perch, and survival and growth of both species was comparable to industry levels. These results validate the effectiveness of mine-water treatment technology; and accordingly, results support commercial viability of crayfish polyculture utilising remediated acid mine water. The large water resources offered by the numerous artificial lakes created from open cut mining has the potential to sustain a large successful aquaculture industry for Collie (Western Australia), and in other areas with extension of water treatment technology.The incorporation of caged silver perch into marron ponds not only takes advantage of the inherent economic and risk-spreading benefits from a diversified management strategy, but also incorporates a number of within-system benefits due to synergism between species. The ecological approach to aquatic polyculture research reported in this thesis has elucidated key communication factors underlying interactions within crayfish polysystems, which is critical to a knowledge-based approach to system management.